Branding Strategies and Digital Journalism for Promoting Sulam Angkinan: An Ethnographic Study in Sungai Lais, Palembang - Ardiansyah, Arif; Suhendra, Suhendra; Laraskana, Tiara Nesva (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2026)
This study addressed the challenges faced by traditional embroidery artisans of Sulam Angkinan in Sungai Lais, Palembang, in gaining public attention and sustaining cultural heritage in the digital age. It aimed to explore how branding strategies and digital journalism through social media serve as tools for cultural empowerment and economic visibility. Employing a qualitative ethnographic approach, the study collected data through in-depth interviews, participant observation, and social media content analysis involving local artisans, community leaders, and digital content creators. The results show that social media storytelling enhances the visibility of Sulam Angkinan and fosters a renewed cultural identity among artisans and their communities. The study concludes that digital journalism, when combined with strategic branding, is a powerful medium to sustain local heritage while reaching wider audiences. These findings contribute to mass communication scholarship by offering a deeper understanding of the intersection between digital media practices and traditional cultural promotion